Optimal prestressing of triple‐bay prestressed stayed columns. (13th September 2017) - Yu, Jialiang; Wadee, M. Ahmer
ABSTRACT: A nonlinear finite element model of the triple‐bay prestressed stayed column is developed within the commercial software ABAQUS. A linearly obtained 'optimal prestress' that maximizes the critical buckling load is investigated since this quantity has been demonstrated in previous work on single‐bay prestressed columns to provide a lower bound to the actual maximum load carrying capacity when compared to results from physical experiments and nonlinear modelling. The ratio of the crossarm to column length, the diameter of the cable stays and the ratio of the prestressing force to the linear optimal prestress are varied. Measures for the relative cost of the main column and the stays are defined and it is determined that the true optimal prestress is generally higher than the linearly obtained quantity but by a reduced factor when compared to an equivalent study for the single‐bay column case.